Snake catcher - Natashah Md. Nor; Rusli Harun; Amelia Abd. Aziz (Malaysia : UAS Communications (M), 1997)
The story of snake catcher in Perlis.
Copy available in DVD format
Executive producer, Najib Shafion, Zabidi Sanip ; script, Amelia Abd. Aziz
Narrator: Reemy Abdul Rahman
Keywords: Snake hunting -- Perlis; Poisonous snakes; Snakes -- Perlis